Review of Brandão de Carvalho, Joaquim, Tobias Scheer and Philippe Ségéral (eds.). 2008. Lenition and fortition. - Kul, Małgorzata; Jaworski, Sylwester (Versita Ltd., de Gruyter, 2011)
Review of Brandão de Carvalho, Joaquim, Tobias Scheer and Philippe Ségéral (eds.). 2008. Lenition and fortition.